2006
DOI: 10.1136/hrt.2005.071860
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of transoesophageal echocardiography before cardioversion in patients with atrial fibrillation and different anticoagulant regimens

Abstract: Objectives: To evaluate the prevalence of atrial thrombi in patients with atrial fibrillation undergoing different anticoagulation regimens before cardioversion; to evaluate the usefulness of transoesophageal echocardiography (TOE) guided cardioversion to prevent thromboembolic complications; and to correlate the presence of atrial thrombi with clinical and echocardiographic data. Methods: 757 consecutive patients admitted as candidates for cardioversion of atrial fibrillation were enrolled in the study. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
0
23
1
1
Order By: Relevance
“…21,28 -33 Though these trials did not directly look at the relationship between the presence of SEC on TEE and postcardioversion thromboembolic risk, they did incorporate a large number of patients with SEC into the cardioversion group (Table I). These studies showed a low thromboembolic risk despite varying methods of anticoagulation, including studies with no or subtherapeutic anticoagulation 28,29,32 prior to cardioversion.…”
Section: Reviews Continuedmentioning
confidence: 99%
“…21,28 -33 Though these trials did not directly look at the relationship between the presence of SEC on TEE and postcardioversion thromboembolic risk, they did incorporate a large number of patients with SEC into the cardioversion group (Table I). These studies showed a low thromboembolic risk despite varying methods of anticoagulation, including studies with no or subtherapeutic anticoagulation 28,29,32 prior to cardioversion.…”
Section: Reviews Continuedmentioning
confidence: 99%
“…TOE is useful in the bedside investigation of thromboembolic events through visualisation of thrombi involving the proximal pulmonary arteries, atheroma plaques (≥ 5 mm) in the thoracic aorta, patent foramen ovale and atrial septal aneurysm [19]. TOE may also visualize thrombi into the main or the right pulmonary artery, then allowing diagnosis of proximal pulmonary embolism at the bedside in a mechanically ventilated patient.…”
Section: The Role For Transoesophageal Echocardiography Investigatingmentioning
confidence: 99%
“…while some data exist to support its use, 22,23 it has been argued that current evidence is insufficient to justify its cost. In addition, TOE may fail to detect small thrombi, TOE examination is labour intensive, and small medical centres may lack the necessary expertise to detect thrombi.…”
Section: Anticoagulation Strategy In Atrial Fibrillation Cardioversionmentioning
confidence: 99%